Secure and Reliable IPTV Multimedia Transmission Using Forward Error Correction - Chi-Huang Shih; Yeong-Yuh Xu; Yao-Tien Wang (International Journal of Digital Multimedia Broadcasting)
With the wide deployment of Internet Protocol (IP) infrastructure and rapid development of digital technologies, Internet Protocol Television (IPTV) has emerged as one of the major multimedia access techniques. A general IPTV transmission system employs both encryption and forward error correction (FEC) to provide the authorized subscriber with a high-quality perceptual experience. This two-layer processing, however, complicates the system design in terms of computational cost and management cost. In this paper, we propose a novel FEC scheme to ensure the secure and reliable transmission for IPTV multimedia content and services. The proposed secure FEC utilizes the characteristics of FEC including the FEC-encoded redundancies and the limitation of error correction capacity to protect the multimedia packets against the malicious attacks and data transmission errors/losses. Experimental results demonstrate that the proposed scheme obtains similar performance compared with the joint encryption and FEC scheme.